2019
DOI: 10.1002/gps.5220
|View full text |Cite
|
Sign up to set email alerts
|

Association between increased theta cordance and early response to ECT in late‐life depression

Abstract: Objectives-More than half of patients with major depression who do not respond to initial antidepressants become treatment resistant (TRD), and while electroconvulsive therapy (ECT) is effective, it involves anesthesia and other medical risks that are of concern in geriatric patients. Past studies have suggested that theta cordance (TC), a correlate of cerebral metabolism measured by electroencephalography, could guide treatment decisions related to patient selection and engagement of the therapeutic target. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Stubbeman and colleagues found an association between clinical response and central cordance ( 26 ). Most recently, in a magnetoencephalography study in late-life depression, no difference was found at baseline between early responders and non-responders in mean frontal theta cordance ( 43 ). These results are contradictory.…”
Section: Discussionmentioning
confidence: 98%
“…Stubbeman and colleagues found an association between clinical response and central cordance ( 26 ). Most recently, in a magnetoencephalography study in late-life depression, no difference was found at baseline between early responders and non-responders in mean frontal theta cordance ( 43 ). These results are contradictory.…”
Section: Discussionmentioning
confidence: 98%
“…The prefrontal theta rhythm has been implicated in neurocognitive processes, such as working memory ( 65 , 66 ) but also in mood control ( 67 ). In particular, the increase of prefrontal activity in the theta band after electroconvulsive therapy ( 68 ) and the increase in frontoparietal connectivity in the theta band after magnetic seizure therapy ( 69 ) have been found to be predictive of treatment response in patients with MDD.…”
Section: Brain State–dependent Stimulation In the Pfcmentioning
confidence: 99%
“…We investigated the prevalence of dementia at This is because HAMD is well known as the rating scale for the late life depression or depression in dementia [18,19], and recommended as the rating…”
Section: Study Proceduresmentioning
confidence: 99%